2020
DOI: 10.1016/j.btre.2020.e00526
|View full text |Cite
|
Sign up to set email alerts
|

Synergic activity of Cel8Pa β-1,4 endoglucanase and Bg1Pa β-glucosidase from Paenibacillus xylanivorans A59 in beta-glucan conversion

Abstract: Highlights Cel8Pa is an extracellular, halotolerant, broad substrate endoglucanase. Bg1Pa is an intracellular β-glucosidase, with activity on cello oligosaccharides and high resistance to ethanol. The concerted action of Cel8Pa and Bg1Pa has a synergistic effect on saccharification of β-glucans. Cel8Pa and Bg1Pa are cold-stable and candidates for SSF ethanol 2 G processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In addition, there are also endoglucanases that have a wider substrate specificity and are active on hemicelluloses like xyloglucan, xylan and arabinoxylan such as the endoglucanase family Cel7, which could explain the low amount of xylose released by EndoB (Vlasenko et al 2010;Hua et al 2018). The levels of the oligosaccharides were higher for the formulations, except for EndoC, which hints to synergistical action of the endoglucanase enzymes with other components of the enzyme formulations like β-glucosidases as reported in previous studies (Song et al 2016;Ghio et al 2020). On the short fiber hardwood pulp, the purified endoglucanases showed a similar pattern as for the long fiber softwood pulp, but a much lower amount of the different sugars was released (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…In addition, there are also endoglucanases that have a wider substrate specificity and are active on hemicelluloses like xyloglucan, xylan and arabinoxylan such as the endoglucanase family Cel7, which could explain the low amount of xylose released by EndoB (Vlasenko et al 2010;Hua et al 2018). The levels of the oligosaccharides were higher for the formulations, except for EndoC, which hints to synergistical action of the endoglucanase enzymes with other components of the enzyme formulations like β-glucosidases as reported in previous studies (Song et al 2016;Ghio et al 2020). On the short fiber hardwood pulp, the purified endoglucanases showed a similar pattern as for the long fiber softwood pulp, but a much lower amount of the different sugars was released (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Moreover, the suppression of its endo-β-1,4-glucanase activity exerted by 2.0 M NaCl was only observed to be approximately 5%, implying that it was a relatively salt-tolerant enzyme. These findings suggested that the salt tolerance of rGluL was superior to that of Paenibacillus xylanivorans A59 GH8 endo-β-1,4-glucanase ( Ghio et al, 2020 ), which showed biocatalytic activity below 50% in the presence of NaCl between 0.5 and 2.0 M.…”
Section: Resultsmentioning
confidence: 99%
“…Figure A shows that the glucose concentration increased at the start but decreased after 12 h, whereas the cellobiose concentration slightly increased at the start but decreased after 8 h. The cellulase enzymes include endoglucanase, exoglucanase (cellobiohydrolase), and β-glucosidase, which act synergistically. The endoglucanase generates reducing and nonreducing chain ends for cellobiohydrolase that releases cellobiose (dimer), which is converted to glucose by β-glucosidase . As Cellic CTec2 has high cellulase and β-glucosidase activities, it produces an elevated level of glucose.…”
Section: Resultsmentioning
confidence: 99%
“…The endoglucanase generates reducing and nonreducing chain ends for cellobiohydrolase that releases cellobiose (dimer), which is converted to glucose by β-glucosidase. 45 As Cellic CTec2 has high cellulase and β-glucosidase activities, it produces an elevated level of glucose. Cellic CTec2 was reported for efficient hydrolysis of hydrothermally pretreated wheat straw.…”
Section: Fermentation Kinetics (Flask)mentioning
confidence: 99%